Somatic Mosaicism of IDH1 R132H Predisposes to Anaplastic Astrocytoma: A Case of Two Siblings - Lee, Sulgi; Kambhampati, Madhuri; Almira-Suarez, M. Isabel; Ho, Cheng-Ying; Panditharatna, Eshini; Berger, Seth I.; Turner, Joyce; Van Mater, David; Kilburn, Lindsay; Packer, Roger J.; Myseros, John S.; Vilain, Eric; et al. (Frontiers in Oncology, 2020)
Anaplastic astrocytomas are aggressive glial cancers that present poor prognosis and high recurrence. Heterozygous IDH1R132H mutations are common in adolescent and young adult anaplastic astrocytomas. In a majority of cases, the IDH1R132H mutation is unique to the tumor, although rare cases of anaplastic astrocytoma have been described in patients with mosaic IDH1 mutations (Ollier disease or Maffucci syndrome). Here, we present two siblings with IDH1R132H mutant high grade astrocytomas diagnosed at 14 and 26 years of age. Analysis of IDHR132H mutations in the siblings’ tumors and non-neoplastic tissues, including healthy regions of the brain, cheek cells, and primary teeth indicate mosaicism of IDHR132H. Whole exome sequencing of the tumor tissue did not reveal any other common mutations between the two siblings. This study demonstrates the first example of IDH1R132H mosaicism, acquired during early development, that provides an alternative mechanism of cancer predisposition.